Problem-Based Learning and Learning Styles: The impact on Student’s Learning Outcomes - Susan Febriantina; Nuryetty Zein; Indah Novita; Marsofiyati4 Marsofiyati4 (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
This study aimed to determine the magnitude of the influence of the problem-based learning model and learning styles on student learning outcomes at SMK Bina Pangudi Luhur Jakarta. The research method used in this study was a survey method with a population of 105 students in the X grade and the sampling technique was proportional random sampling. The result was a significant direct and indirect influence between the problem-based learning model on student learning outcomes, learning styles on learning outcomes, the problem-based learning model on student learning styles, as well as the problem-based learning models and learning styles on the learning outcomes of students of class X at SMK Bina Pangudi Luhur Jakarta. In addition to the problem-based learning model and learning style, student learning outcomes were also influenced by other factors. Therefore, further research can examine more closely the other factors that influence student learning outcomes.